Practical Steps for Bibliometric Analysis: Mapping Trends in Scientific Articles on Digital Literacy Using VOSviewer from the Google Scholar Database - Rohmani, Rohmani; Suprapto, Irawan; Pambudi, Nanda (International Journal of Multidisciplinary Approach Research and Science, 2024)
The Google Scholar database has become an indispensable resource for article search in the digital age. The purpose of this study was to examine articles from the Google Scholar database and demonstrate how to use VOSviewer to analyze bibliometric data. Users are given an initial explanation of step-by-step analysis using VOSviewer to make it easier to map research trends. The study offers analytical findings from the growing digital literacy research and explains how simple it is to evaluate data using mapping tools. As a starting point for future research, bibliometric analysis is used in this research to uncover trends and patterns in the development of science. For example, concrete publications on digital literacy involve the collection of 204 published documents from 2018 to 2022. The results of mapping with VOSviewer can be used to offer recommendations in the results of data analysis to identify research trends. Some keywords that become opportunities for future research trends related to digital literacy are models, PBL, children's digital literacy, hoaxes.